2006
DOI: 10.1111/j.1444-2906.2006.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent index of mitotic interval τ0 in greenling Hexagrammos otakii

Abstract: The aim of this study was to establish effective procedures for chromosome manipulation in greenling Hexagrammos otakii Jordan et Starks, which has enormous aquacultural potential. To accomplish this, temperature-dependent measurements of the mitotic intervals (τ 0 ) were carried out. The τ 0 in this fish was determined by averaging the duration of the first and third embryonic divisions at temperatures ranging 5-25°C. At higher temperatures, eggs developed faster and underwent more identical development. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Temperaturedependence of τ 0 in black plaice is similar to observations for winter flounder (Pseudopleuronectes americanus; Park and Johnson, 2002), far eastern catfish (Silurus asotus; Park and Im, 2001), greenlings (Hexagrammos otakii; Park et al, 2006), baltic herring (Clupea harengus membras; Saat and Veersalu, 1996b), perch (Perca fluviatilis; Saat and Veersalu, 1996a), and ruffe (Gymnocephalus cernuus; Saat and Veersalu, 1996a). Additionally, the relationships between τ 0 and water temperature in fish are typically curvilinear, providing that temperatures are within the range for which the species of fish naturally spawns and develops Veersalu, 1996a, 1996b;Park and Im, 2001;Park and Johnson, 2002;Park et al, 2006). Observed linear relationship between τ 0 and temperature was consistent with data for the developmental rates of black carp and winter flounder (Shelton and Rothbard, 1993;Park and Johnson, 2002).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Temperaturedependence of τ 0 in black plaice is similar to observations for winter flounder (Pseudopleuronectes americanus; Park and Johnson, 2002), far eastern catfish (Silurus asotus; Park and Im, 2001), greenlings (Hexagrammos otakii; Park et al, 2006), baltic herring (Clupea harengus membras; Saat and Veersalu, 1996b), perch (Perca fluviatilis; Saat and Veersalu, 1996a), and ruffe (Gymnocephalus cernuus; Saat and Veersalu, 1996a). Additionally, the relationships between τ 0 and water temperature in fish are typically curvilinear, providing that temperatures are within the range for which the species of fish naturally spawns and develops Veersalu, 1996a, 1996b;Park and Im, 2001;Park and Johnson, 2002;Park et al, 2006). Observed linear relationship between τ 0 and temperature was consistent with data for the developmental rates of black carp and winter flounder (Shelton and Rothbard, 1993;Park and Johnson, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Fish were weighed to the nearest 0.01 g using an electronic balance (JW-1; Acom, Pocheon, Korea), and body lengths were measured to the nearest 0.01 cm using digital vernier calipers (CD-20CP; Mitutoyo, Kawasaki, Japan). Sperm and eggs were artificially fertilized using the dry process (Park et al, 2006).…”
Section: Broodstock and Artificial Fertilizationmentioning
confidence: 99%
“…To date, several reports are available on reproduction (Wen, Wang, Mou, Chen, Yao & Chen ; Pan, Hu, Gao, Jian, Zhang, Wang & Guo ), development (Park, Kim, Woo, Oh, Kim & Hur ; Lee & Cho ), feeding physiology (Kim & Kang ; Kwak, Baecka & Klumppb ), disease (Ki, Kyoung & Chun ; Park, Jo, Lee, Kim, Park, Hur, Yoo & Song ), nutritional composition (Masahiro, Yasuyuki & Atsunobu ) and polymorphic microsatellites (Chen, Miao, Shao, Tian & Liao ) of H. otakii . However, very little is known about the biological and ecological requirements of this species as a basis for fishery management, commercial cultivation and replenishment of natural populations.…”
Section: Thp Vnh Larvae 24 H Post Hatch Tmp and Dp For Hexagrammos mentioning
confidence: 99%
“…The greenling is a number of the typical seawater Hexagrammidae and a commercially important greenling species, and this species is a favorite seawater food fish because of its taste and tender meat [7]. Previous study reported the anesthesia effects of MS-222 and lidocaine-HCl on the greenling [3].…”
Section: Introductionmentioning
confidence: 99%
“…The greenling, Hexagrammos otakii (Jordan and Starks) is commonly found in coastal areas of Korea throughout the year [7]. The greenling is a number of the typical seawater Hexagrammidae and a commercially important greenling species, and this species is a favorite seawater food fish because of its taste and tender meat [7].…”
Section: Introductionmentioning
confidence: 99%